The Impact of Parent-led Dialogic Reading on English and Spanish Vocabulary - Williams, Janet D. (My University, 2019)
Vocabulary development plays an important role in pre-literacy skills. Children who are learning two languages often lag behind their peers in vocabulary skills, thus making them at risk for academic struggles. Previous research supports the use of dialogic reading interventions as a way to improve vocabulary skills. The home environment serves as a feasible place for children to learn new words through the practice of dialogic reading with their caregivers. The purpose of this study was to investigate the effectiveness of a dialogic reading intervention, in the primary language of Spanish, on the acquisition of vocabulary skills in Spanish and English. The interventions were provided in Spanish to an intervention group of seven students, while eight other students were in the control group. The focus of the intervention was to train parents of bilingual preschoolers who were enrolled in Head Start ways to increase vocabulary development through the use of dialogic reading. Direct, in-person, training was offered to the caregivers in English and Spanish. In addition, all correspondence was given in English and Spanish, including on-line videos demonstrating dialogic reading. Caregivers were asked to implement the interventions three times a week for a total of eight weeks. While there was no statistical significance between the intervention and control groups, there were individual improvements in vocabulary skills among the participants.
I. INTRODUCTION 1 -- II. REVIEW OF THE LITERATURE 5 -- Hispanic population in the United States 5 -- Cultural and Socio-economic aspects of the Hispanic population 6 -- Academic challenges and risk factors for Hispanic students 9 -- Language Development 11 -- Neuroscience of bilingualism 15 -- Fast mapping and working memory in language acquisition 16 -- Development of language in bilingual speakers 19 -- Affective variables in language acquisition 21 -- Language and cultural differences that could impact academics 22 -- Language of intervention 26 -- Importance of family literacy experiences 30 -- Book reading among cultures 31 -- Reading styles 33 -- Conceptual Framework of the Intervention 35 -- The intervention of dialogic reading 37 -- Definitions of PEER, CROWD approaches 41 -- Benefits of dialogic reading 42 -- Dialogic reading and children with language impairments 48 -- Dialogic reading and English language learners 49 -- Book selection 54 -- Length of intervention 56 -- Training of caregivers (live vs. video) 56 -- Improves children’s enjoyment of reading 57 -- Low cost and home-based 58 -- Use of interpreter 58 -- Incorporate triadic strategies to include an interpreter, parent-training, and relations with the one providing interventions 59 -- Purpose of the study 60 -- Independent /dependent variables 62 -- III. METHODOLOGY 64 -- Participants 64 -- Materials 66 -- Procedures 68 -- IV. RESULTS 74 -- Introduction 74 -- Results of Parental Surveys 74 -- Receptive Vocabulary Test Scores 76 -- Individual Participant Data 82 -- Bilingual vs. Primary Spanish comparisons 83 -- Fidelity, Validity, and Reliability 86 -- Social Validity 86 -- V. DISCUSSION 88 -- Analysis of individual participants 88 -- Parental survey analyses 91 -- Limitations 92 -- Recommendations for future research 94 -- VI. CONCLUSION 96 -- VII. REFERENCES 98 -- Appendix A: Institutional Review Board Approval 118 -- Appendix B: Letter of Approval 124 -- Appendix C: Parent Permission and Child Assent Form (English and Spanish) 126 -- Appendix D: Telephone Scripts in English and Spanish 134 -- Appendix E: Parent Questionnaire (English and Spanish) 137 -- Appendix F: List of books used in the study 140 -- Appendix G: Reading Log 142 -- Appendix H: CROWD and PEER (English and Spanish) 144 -- Appendix I: Example of Script for a book (English and Spanish translations) 149 -- Appendix J: Fidelity Checklist 153 -- Appendix K: Post-Intervention Survey for Parents 155.
Keywords: Dissertations, Academic--United States; Reading (Early childhood); Reading comprehension--Study and teaching; Spanish language--Study and teaching; Children--Language; Vocabulary--Study and teaching; English language--Study and teaching; Reading (Preschool); Preschool children; Bilingualism; Bilingualism in children